Biomedical engineering approaches for the delivery of JAGGED1 as a potential tissue regenerative therapy - Kaimari, Sundus; Kamalakar, Archana; Goudy, Steven L. (Frontiers in Bioengineering and Biotechnology, 2023)
JAG1 is a ligand that activates the NOTCH signaling pathway which plays a crucial role in determining cell fate behavior through cell-to-cell signaling. JAG1-NOTCH signaling is required for mesenchymal stem cell (MSC) differentiation into cardiomyocytes and cranial neural crest (CNC) cells differentiation into osteoblasts, making it a regenerative candidate for clinical therapy to treat craniofacial bone loss and myocardial infarction. However, delivery of soluble JAG1 has been found to inhibit NOTCH signaling due to the requirement of JAG1 presentation in a bound form. For JAG1-NOTCH signaling to occur, JAG1 must be immobilized within a scaffold and the correct orientation between the NOTCH receptor and JAG1 must be achieved. The lack of clinically translatable JAG1 delivery methods has driven the exploration of alternative immobilization approaches. This review discusses the role of JAG1 in disease, the clinical role of JAG1 as a treatment, and summarizes current approaches for JAG1 delivery. An in-depth review was conducted on literature that used both in vivo and in vitro delivery models and observed the canonical versus non-canonical NOTCH pathway activated by JAG1. Studies were then compared and evaluated based on delivery success, functional outcomes, and translatability. Delivering JAG1 to harness its ability to control cell fate has the potential to serve as a therapeutic for many diseases.